Guide to computer forensics and investigations - Nelson, Bill; Phillips, Amelia ;Steuart, Christopher (Australia : Cengage Learning Asia Pte Ltd, 2010)
Helps learners master the skills necessary to launch and complete a successful computer investigation. This resource guides them through conducting a high-tech investigation, from acquiring digital evidence to reporting its findings. It features free downloads of the forensic software, so readers can become familiar with the tools of the trade.
Chapter 1: Computer Forensics and Investigation Processes -- Chapter 2: Understanding Computing Investigations -- Chapter 3: The Investigator's Office and Laboratory -- Chapter 4: Data Acquisitions -- Chapter 5: Processing Crime and Incident Scenes -- Chapter 6: Working with Windows and DOS Systems -- Chapter 7: Current Computer Forensics Tools -- Chapter 8: Macintosh and Linux Boot Processes and File Systems -- Chapter 9: Computer Forensics Analysis -- Chapter 10: Recovering Graphics Files -- Chapter 11: Virtual Machines, Network Forensics, and Live Acquisitions -- Chapter 12: E-mail Investigations -- Chapter 13: Cell Phone and Mobile Device Forensics -- Chapter 14: Report Writing for High-Tech Investigations -- Chapter 15: Expert Testimony in High-Tech Investigations -- Chapter 16: Ethics and High-Tech Investigations.
Includes index.
Keywords: COMPUTER SECURITY